The Impact of Perceived Organizational Support and Job Involvement To Employee Loyalty in Pt. Bank Rakyat Indonesia of Kebayoran Baru Branch Office - Nur Asni Gani; Hilwah Farhati; Andry Priharta; Darto Darto; Bambang Sutrisno (Business and Entrepreneurial Review, 2021)
The purpose of this study is to measure the impact of Perceived Organizational Support and Job Involvement on Employee Loyalty at PT. Bank Rakyat Indonesia (BRI), the Kebayoran Baru Branch office. The research method is quantitative with data collection through a survey using Google Forms distributed to employees of PT. Bank BRI Kebayoran Baru branch office with a total population of 193 and determining a sample with the Slovin formula as many as 45 respondents. The results showed that Perceived Organizational Support had an impact on employee loyalty and job involvement had an impact on employee loyalty. This research implies that PT. Bank BRI provides support to employees and involves employees in company activities, so that employees feel involved, and creates employee loyalty at Bank BRI Kebayoran Baru branch office.